ANALYSIS OF LITERARY TEXTS IN AFGHAN STAGE EVENTS FROM THE PERSPECTIVE OF ART ANTHROPOLOGY (STUDY OF AFGHAN FILM STAGE EVENTS) - Dadman, Enayatullah; Maroofi, Safiullah; Stanikzai, Sultan Mohammad (CV. Radja Publika, 2023)
The arts have drawn from many sources throughout history. Some like cinema more and others less. It seems. Literature has been one of the sources for adaptation in photography. But is it really possible to adapt literature and literary sources in photography and if so, how? literary text has a hug impact on reading ability and fully understand the text. In this paper, using a descriptive-context-analytical method, with the perspective of art anthropology.as a result Adaptation from literary sources is possible in text, but it is seen more in staged literary texts, and text writers have adapted more from literary texts than from prose, and the reason for this is that it is possible to adapt more freely than poetry. In order to be represented by literary texts, literary texts must have the capacity to create space, personify, and narrate. However, writers mostly use their mental and inner perception during text writings.